The effect of eggs on early child growth in rural Malawi: the Mazira Project randomized controlled trial. Issue 4 (6th August 2019) - Stewart, Christine P; Caswell, Bess; Iannotti, Lora; Lutter, Chessa; Arnold, Charles D; Chipatala, Raphael; Prado, Elizabeth L; Maleta, Kenneth
ABSTRACT: Background: Stunted growth is a significant public health problem in many low-income countries. Objective: The aim of this study was to evaluate the impact of 1 egg per day on child growth in rural Malawi. Design: We conducted an individually randomized controlled trial in which 660 children aged 6–9 mo were equally allocated into an intervention (1 egg/d) or control group. Eggs were provided during twice-weekly home visits for 6 mo. Control households were visited at the same frequency. Assessors blinded to intervention group measured length, weight, head circumference, and midupper arm circumference at baseline and the 6-mo follow-up visit. To assess adherence, multipass 24-h dietary recalls were administered at baseline, 3-mo, and 6-mo visits. Results: Between February and July 2018, 660 children were randomly assigned into the intervention ( n  = 331) and control ( n  = 329) groups. Losses to follow-up totaled 10%. In the intervention group, egg consumption increased from 3.9% at baseline to 84.5% and 70.3% at the 3-mo and 6-mo visits, whereas in the control group, it remained below 8% at all study visits. The baseline prevalence of stunting was 14%, underweight was 8%, and wasting was 1% and did not differ by group. There was no intervention effect on length-for-age, weight-for-age, or weight-for-length z scores. There was a significantly higher head circumference for age z score of 0.18 (95% CI: 0.01, 0.34) in the egg group compared with the control group. There was a significant interaction with maternal education ( P  = 0.024), with an effect on length-for-age z score only among children whose mothers had higher education. Conclusions: The provision of 1 egg per day to children in rural Malawi had no overall effect on linear growth. A background diet rich in animal source foods and low prevalence of stunting at baseline may have limited the potential impact. This trial was registered at clinicaltrials.gov as NCT03385252.